2015
DOI: 10.12988/ijcms.2015.5210
|View full text |Cite
|
Sign up to set email alerts
|

Alternative ridge robust regression estimator for dealing with collinear influential data points

Abstract: The multicollinearity in multiple linear regression models and the existence of influential data points are common problems. These problems exert undesirable effects on the least squares estimators. So, it is very important to introduce some alternative biased estimators of the robust ridge regression to overcome the influence of these problems simultaneously. In this paper, alternative biased robust regression estimator is defined by mixing the ridge estimation technique into the robust least median squares e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Mansson and Shukur [19] have investigated some logistic ridge regression parameters and they have shown that there is at least one ridge regression estimator that has a lower mean square error than the maximum likelihood method for all situations. Salam [20] has introduced an alternative procedure having a smaller mean square error for determining the ridge parameter. Khalaf [21] proposes two ridge regression parameters and demonstrates the performance of the proposed estimators outperforming the OLS and other estimators.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mansson and Shukur [19] have investigated some logistic ridge regression parameters and they have shown that there is at least one ridge regression estimator that has a lower mean square error than the maximum likelihood method for all situations. Salam [20] has introduced an alternative procedure having a smaller mean square error for determining the ridge parameter. Khalaf [21] proposes two ridge regression parameters and demonstrates the performance of the proposed estimators outperforming the OLS and other estimators.…”
Section: Literature Reviewmentioning
confidence: 99%